Telegraph noise and the Fabry-Perot quantum Hall interferometer - Rosenow, B; Simon, S (2012)
We consider signatures of Abelian and non-Abelian quasiparticle statistics in quantum Hall Fabry-Perot interferometers. When quasiparticles enter and exit the interference cell, for instance due to glassy motion in the dopant layer, the anyonic phase can be observed in phase jumps. In the case of the non-Abelian ν=5/2 state, if the interferometer is small, we argue that free Majoranas in the interference cell are either strongly coupled to one another or are strongly coupled to the edge. We analyze the expected phase jumps and in particular suggest that changes in the fermionic parity of the ground state should gives rise to characteristic jumps of π in the interference phase. © 2012 American Physical Society.